A Review on Brain Implants - Satheesan, A Dilna (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 5 No 1 (2021): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
The utilization of artificial gadgets to control the working of different parts in a person has seen an upsurge in the most recent decade, which has prompted voluminous consultations and suspicion. This paper presents a thorough conversation of a few tests led on cerebrum embeds, their outcomes, research holes, conceivable future progressions, and the neuro-moral vantage point for proceeded with utilization of brain implants in patients. Brain Implants helps in solving problems like motor-neuron problem. It has been proved by scientific studies that it improves human memory. It can be used to solve problems of time inefficiency in communication, and it is also used to solve problems related to spine. The implementation of optimized neuromorphic hardware as a highly promising solution for future ultra-low-power cognitive systems. Treat brain disorders, and then ultimately to enhance our brains to create a sort of "symbiosis" with artificially intelligent machines Brain Implants are of following types: Deep Brain Stimulation, Stentrode, Bioresorbable implants. By exploring various brain-inspired technologies and knowing its benefits to humans, it sort of gives human body superpowers, it is expected to see more growth in the sector of Brain Chip Implants. How to cite this article: Satheesan AD, Deshmukh C, Dwivedi A et al. A Review on Brain Implants. J Adv Res Appl Arti Intel Neural Netw 2021; 5(1): 15-21